Efficient extraction of nickel from sintered alloy by stepwise leaching: Thermodynamic and kinetic studies. (September 2022) - Han, Junwei; Wang, Yongwei; Mao, Xiaohui; Chang, Xuejie; Zeng, Hongbo; Qin, Wenqing
Graphical abstract: Highlights: More than 99.9% Ni was extracted from sintered alloy by stepwise leaching process. Nickel oxides and passivation films prevented high-efficient extraction of nickel. The nickel oxides were converted into water-soluble NiSO4 by an acid curing process. The leaching process was controlled by the mixed control model within 60 min. Abstract: Atmospheric acid leaching is widely used to extract nickel from secondary resources due to its mild effect, but the extraction efficiency of nickel still remains limited. In this work, a sulfuric acid curing process was developed to improve the extraction of nickel by treating the leaching residues after acid leaching. The factors influencing the extraction of nickel from sintered alloy have been systematically studied based on thermodynamic calculations. The results show that the extraction of nickel reached 80.34 % after acid leaching under the optimized conditions. Reaction kinetic studies indicate that the leaching process was governed by a combination of the mixed control model (0–60 min) and the surface chemical reaction control model (60–100 min), with the apparent activation energies of these two stages determined as 33.32 and 67.07 kJ/mol, respectively. The X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), and scanning electron microscopy coupled with energy dispersive X-ray spectroscopy (SEM-EDS) analyses indicate that the NiO coated by Ni2 O3 in the sintered alloy and NiO passivation films generated during the acid leaching process hindered further dissolution of metallic nickel. The nickel oxides and passivation films could be transformed into water-soluble NiSO4 after sulfuric acid curing with 60 % H2 SO4 solution at 140 ℃. The overall extraction efficiency of nickel can reach as high as 99.13 % by using the two-stage leaching developed. This work provides a feasible and highly efficient approach to extract nickel from sintered alloy.